Pelayanan Publik Melalui Sistem E-Filling di Kantor Pelayanan Pajak Pratama Cilegon - Nurfatma Asriyanti; Arif Nugroho; Racmi Yulianti (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2020)
This study aims to determine Public Services through the E-filling System at the Cilegon Primary Tax Service Office and to determine the supporting and inhibiting factors. The research used is a descriptive qualitative approach. The data sources used are primary and secondary data. To deepen the data analysis interviews, observation, and documentation were carried out. The theoretical basis used is public service. The results showed that the public service through the e-filling system was running well-reviewed with the theory of public service. But there are several supporting and inhibiting factors found. Supporting factors 1) employee upgrading, 2) socialization. The inhibiting factors are 1) lack of human resources, 2) e-filling applications are down or error